Influence of mountain bike riding velocity, braking and rider action on pedal kickback - Gerth, M.; Haecker, M.; Kohmann, P. (Sports Engineering, 2020)
When dealing with full suspension mountain bikes, pedal kickback is one of the main parameters used to assess the performance of rear wheel kinematics. According to the currently used theory of Kovács, pedal kickback is the backwards rotation of the crank during the compression of the rear suspension, which mainly occurs because of elongation between the bottom bracket and the rear axle. Most bike companies try to minimize pedal kickback during kinematic design, because this phenomenon creates unwanted harshness in the suspension and negatively influences rider stability due to the backwards rotation of the crank. When riding downhill above a certain velocity (i.e., the critical velocity) without pedaling or blocking the rear wheel, the cassette will complete a forward rotation instead of a backwards rotation of the crank, which is hereinafter referred to as freewheel theory. The cassette will perform this forward rotation without affecting the rider or creating suspension harshness. The paper discusses the analytical derivation for the calculation of the linearized critical velocity and presents a multibody simulation to calculate the exact critical velocity. The existence of the critical velocity is shown through measurements with an instrumented bike during a test ride on a downhill track and through an experiment performed under idealized conditions. The test ride demonstrated the influence of the rider on the critical velocity by moving the cranks in certain riding situations, such as landing on the front wheel first or hitting large obstacles. The crank movement leads to an increased (forward rotation) or decreased (backwards rotation) critical velocity. Both riding situations are reproduced with the multibody simulation.